Functional evaluation of transplanted kidneys using arterial spin labeling MRI. Issue 1 (7th October 2013) - Heusch, Philipp; Wittsack, Hans‐Jörg; Blondin, Dirk; Ljimani, Alexandra; Nguyen‐Quang, Michael; Martirosian, Petros; Zenginli, Hakan; Bilk, Philip; Kröpil, Patric; Heusner, Till A.; Antoch, Gerald; Lanzman, Rotem S.
Abstract : Purpose: To investigate non–contrast‐enhanced arterial spin labeling (ASL) MRI for functional assessment of transplanted kidneys at 1.5 Tesla (T) and 3T. Materials and Methods: This study was approved by the local ethics committee, and written informed consent was obtained from all participants. Ninety eight renal allograft recipients (mean age, 51.5 ± 14.6 years) were prospectively included in this study. ASL MRI was performed at 1.5T (n = 65) and 3T (n = 33) using a single‐slice flow‐sensitive alternating inversion recovery true–fast imaging with steady‐state precession (FAIR True‐FISP) sequence in the paracoronal plane. ASL perfusion was regional analyzed for the renal cortex on parameter maps. ASL was compared between patients with good or moderate allograft function (Group a; estimated glomerular filtration rate [eGFR] > 30 mL/min/1.73 m 2 ) and patients with heavily impaired allograft function (Group b; eGFR ≤ 30 mL/min/1.73 m 2 ) and correlated to renal function as determined by eGFR. Results: ASL perfusion and eGFR were comparable at 1.5T (246.9 ± 66.8 mL/100 g/min and 41.9 ± 22.7 mL/min/1.73 m 2 ) and 3T (236.5 ± 102.3 mL/100 g/min and 35.9 ± 22.9 mL/min/1.73 m 2 ). ASL perfusion was significantly higher in group a (282.7 ± 60.8 mL/100 g/min) as compared to group b (178.2 ± 63.3 mL/100 g/min) ( P < 0.0001). ASL perfusion values exhibited a significant correlation with renal function as determined by eGFR (r = 0.59; P < 0.0001). Conclusion: Cortical ASL perfusion values differ between patients with good or moderate allograft function and poor allograft function and correlate significantly with allograft function. Our results highlight the potential of ASL MRI for functional evaluation of renal allografts.J. Magn. Reson. Imaging 2014;40:84–89 . ©2013 Wiley Periodicals, Inc .